THE ROLE OF GOVERNMENT BODIES IN THE DEVELOPMENT OF FREE ECONOMIC ZONES - Makhsudov Sherzod Solijonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the issues of increasing the efficiency of free economic zones. Effective functioning of the FEZ management bodies Conclusions are drawn on improving the specialization of the FEZ in the country.